The Future of the Academic Journal. - Cope, Bill (Elsevier Science, 2014)
The world of the academic journal continues to be one of radical change. A follow-up volume to the first edition of The Future of the Academic Journal, this book is a significant contribution to the debates around the future of journals publishing. The book takes an international perspective and looks ahead at how the industry will continue to develop over the next few years. With contributions from leading academics and industry professionals, the book provides a reliable and impartial view of this fast-changing area. The book includes various discussions on the future of journals, inc.